GAMBARAN KETERSEDIAAN PANGAN DAN STATUS GIZI ANAK BALITA PADA KELUARGA PEROKOK DI DESA TRANS PIRNAK MARENU KECAMATAN AEK NABARA BARUMUN KABUPATEN PADANG LAWAS - Mariana Siregar; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Mother and children under five group of people who are sensitive to issues of food available. Desa Trans Pirnak Marenu including food insecure areas with population worked as farmers manyoritas. The objective of this  study is to determine the existence supply of food  and nutritional status on those head of household as  smoker family at Desa Trans Pirnak Marenu. This study is a survey research with cross sectional approach. . Population involved those smoking members having children under five years. As primary data, collected with questionnaire consisting of available foods, and smoker family in the village of Trans Pirnak Marenu then analyzed descriptively and presented in the form of cross-tabulation and frequency distribution table. The results  showed levels of food availability by cigarette spending most (78.9%) of food insecurity with hunger as much as 21.2% mild, moderate hunger as much as 32.7%, and the rate of severe hunger as much as 25.0%. Spending smaller cigarette, food availability is assured as much as 27.6%, while expenditure cigarette, food availability is assured as much as 13.0%. and acute and chronic malnutrition is still common in families of smokers. In this research showed more correlation be encouraged in sector cross in order to provide them personally counseling, about health, and the dangerous of smoking, it shhould be enlarge promoted to all families having children under five years, this in order to improve consumption of nutritious and balanced food. Keywords : Food available, nutritional status children under Five years, smoker family